2004
DOI: 10.1002/ajmg.a.30015
|View full text |Cite
|
Sign up to set email alerts
|

Twenty‐four new cases of WT1 germline mutations and review of the literature: Genotype/phenotype correlations for Wilms tumor development

Abstract: We report here 24 new Wilms tumor (WT) patients with germline WT1 alterations and a synopsis of our own previously described and literature cases in whom age of tumor-onset, gender, and laterality were known. This combined database contains 282 patients, 117 patients with and 165 without WT1 germline alterations. Using this information we have determined the median age of tumor-onset for patients with (12.5 months) and without WT1 gene alterations (36 months). The earliest onset was in patients with truncation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
85
2
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(96 citation statements)
references
References 50 publications
7
85
2
2
Order By: Relevance
“…Because of the different approach, our cohort also includes a small subset of patients without proteinuria. Some of our findings are in line with the previously published literature, such as the association of age at proteinuria onset and the initiation of RRT, as well as frequency and bilateralism of WT with type and location of the causative mutation (20,21).…”
Section: Discussionsupporting
confidence: 92%
“…Because of the different approach, our cohort also includes a small subset of patients without proteinuria. Some of our findings are in line with the previously published literature, such as the association of age at proteinuria onset and the initiation of RRT, as well as frequency and bilateralism of WT with type and location of the causative mutation (20,21).…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, it could be questioned whether all bilateral Wilms tumors in nonsyndromic patients should be screened on germline mutations of WT1, as we did in our patient. Our patient revealed a germline splice site mutation in [2,7,24,26]. However, Schumacher et al [26] found that an extensive rhabdomyomatous diVerentiation and the presence of WT1 mutations correlate with a tumor subtype that responds poorly to chemotherapy.…”
Section: Discussionmentioning
confidence: 64%
“…It is estimated that in at least 10% of all Wilms tumor cases, the disease arises in children with clinically well-deWned genetic conditions, including WAGR, Denys-Drash, and Beckwith-Wiedemann syndrome [1,3,15,18,23,27]. It has been suggested that nonsyndromic Wilms tumor patients carry a higher risk of germline WT1 mutations in case of bilateral disease and an early age of onset [24]. In contrast, Perotti et al [23] concluded that early age of diagnosis and bilaterality in Wilms tumor patients without associated abnormalities are no eYcient predictors of germline WT1 aberrations, based on a small group of 20 tumors with only 9 bilateral tumors [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Renal histology revealed that most glomeruli (77.9%) were in an early stage of DMS. The mutation she carried is also a novel mutation for a DDS patient, although it had been reported in some Wilms' tumor patients 14 and in a 46 XY male Frasier syndrome patient. 15 Therefore, it seems that the mutation at this site can cause a broad range of clinical phenotypes.…”
Section: Discussionmentioning
confidence: 94%